Methodology to evaluate the impact on local development of the master’s program in management accounting of the University of Holguin, Cuba - Sánchez Arencibia, Alba; Laguna Cruz, Jorge Alejandro; Téllez Sánchez, Lino (Avances en Supervisión Educativa, 2018)
The authors present the results obtained with the elaboration and application of a methodology to evaluate the changes observed in the students and in their organizations, by the effect of the formative actions of the Master’s program in Management Accounting of the University of Holguin, according to the requirements of the impact achieved, depending on the needs of human resources for local development. The methodology created in a participatory action research process is explained, through a system of meetings and methodological exchanges developed with teachers, tutors, employers, graduates and students of the master’s program. The authors executed the research according to the requirements of the University System of Accreditation Programs (SUPRA), and of the results of the diagnosis made, as part of the self-assessment with a view to continuous improvement, which made it possible to evaluate the relevance and feasibility of the methodology, supported by the favorable consensus of teachers and tutors, with regard to its coherence and applicability.